The Arab revolution ten lessons from the democratic uprising - Filiu, Jean-Pierre (Comparative politics and international studies series, 2011)
This is a concise, but sweeping account of the earth-shattering revolts that began in Tunis in 2010 and continue today throughout the Middle East. Stressing deep historical roots of the events, the author organizes the book around ten lessons that illuminate both the uprisings in particular and the region in general. He touches on the long fight for rights, the role of youth, the role of social networks, power, anger, the difficult position jihadists are now in, and how Palestine remains the central concern throughout the Middle East.